Indirect Matrix Converter Based Synchronous Reluctance Motor Drive Systems using Model Predictive Control - Laksmi B., Nur Vidia; Mubarok, Muhammad Syahril; Aribowo, Widi; Purwanto, Didik; Isaac, Jacob Raglend; Abdullayev, Vugar Hacimahmud (Universitas Ahmad Dahlan, 2026)
This paper proposes a speed control strategy of Synchronous Reluctance Motors (SynRM) using an Indirect Matrix Converter (IMC) combined with a finite model predictive speed control (MPSC) and PI current control. This control algoritm is chosen than fully PI in both loops due to improve overall system stability and dynamic response. The IMC architecture offers advantages such as compactness, bidirectional power flow, and the elimination of bulky passive components, making it ideal for efficient motor drive systems. The proposed control method employs predictive algorithm using augmented state variable and cost function minimization technique. In addition, PI controllers here using a pole-assignment method. Both proposed controls aim to guarantee stability and responsiveness for dynamic performances. The MATLAB/Simulink is used here to simulate the system, incorporating practical motor parameters and space vector modulation techniques. Simulation results show that the control algorithm attains satisfactory speed performance, with minimal steady-state error 0.47%, overshoot below 2%, and fast settling time under various load 0.035 seconds and speed profiles. Additionally, the system performs robustly under reversed and sinusoidal speed commands, demonstrating its effectiveness and suitability for real-world industrial applications also need to implement in the experiment for the future works.